Toward highly efficient cell-type-specific gene transfer with retroviral vectors displaying single-chain antibodies. - Chu, T H (1997)
Recently, we constructed retroviral vector particles derived from spleen necrosis virus (SNV) that display a single-chain antibody (scA) on the viral surface. By transient transfection protocols, we showed that such particles are competent for infection and cell type specific. Efficient infection was dependent on the presence of wild-type envelope, although wild-type SNV was not infectious on target cells (T.-H. T. Chu and R. Dornburg, J. Virol. 69:2659-2663, 1995; T.-H. T. Chu, I. Martinez, W. C. Sheay, and R. Dornburg, Gene Ther. 1:292-299, 1994). In this study, stable packaging lines were constructed and detailed biological and biochemical studies were performed. Chimeric scA-envelope fusion proteins were expressed as efficiently as wild-type envelope and were stable over a period of at least 6 h. Only a fully functional wild-type envelope could act as a helper for efficient virus penetration. The ratio of wild-type envelope protein to chimeric envelope protein appears to determine the efficiency of infection. Virus titers of targeting vectors obtained from stable packaging lines were as high as 10(4) CFU/ml. A 25-fold concentration of vector virus stocks resulted in a 200-fold increase in virus titers (up to 10(6) CFU/ml). These data indicate that an inhibitor of infection was (at least partially) removed by the concentration protocol. Our data show that this technology has several variables for further improvements and, therefore, has the potential to become a powerful tool for cell-type-specific in vivo human gene therapy.